Nitrile Synthesis through Catalyzed Cascades Involving Acid–Nitrile Exchange - Cartigny, Damien; Dos Santos, Aurélie; El Kaïm, Laurent; Grimaud, Laurence; Jacquot, Roland; Marion, Philippe (Synthesis, 2014)
Irreversible acid–nitrile exchange reactions using both glutaronitrile and (phenylsulfonyl)acetonitrile may be catalyzed by Lewis acids. Whereas a cyclization towards imides displaces the equilibria in the reaction with dinitriles, a decarboxylation step is involved when using the (phenylsulfonyl)acetonitrile.
Keywords: acylation; carboxylic acids; nitriles; imides; Lewis acids